Effects of mineral and organic fertilization with the use of wet olive pomace on durum wheat performance - Giovanni Lacolla; Stefania Fortunato; Domenica Nigro; Maria Concetta De Pinto; Mario Alberto Mastro; Davide Caranfa; Agata Gadaleta; Giovanna Cucci (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Despite durum wheat accounts for only 5% of the global wheat production, it represents an economically important species, as a basic food and primary source of daily caloric intake in the Mediterranean basin area. By-products of agricultural processing, such as pomace, can be used to increase soil fertility, as they are indeed a source of important nutrients useful for crop growth. Method The present research was carried out on durum wheat, as part of a long-term experiment. The study aimed at assessing the effects of mineral and organic fertilization with the use of wet olive pomace on a 3-year trial with crops grown in succession (fava beansâwheatâspelt). A split-plot experimental design with three replicates was used. The cultivars (Aureo and Vespucci) were assigned to the main plots and the seven fertilization treatments to the sub-plots. Results Our result showed that supplying wet olive pomace as soil improver was not sufficient to significantly improve soil fertility compared to the unfertilized control. However, when 60 kg haâ1 of nitrogen was supplied in coverage before tillering, in addition to 70 Mg haâ1 of wet olive pomace yield an increase of 66% in Aureo cv and of 222% in Vespucci cv, in comparison to the unfertilized crop. Conclusion The best management of fertilizers, associated with the use of more nitrogen-use-efficient genotypes, is essential for the development of a sustainable agriculture.